1984
DOI: 10.1111/j.1748-1716.1984.tb07417.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal excretion of prostaglandin metabolites, arginine vasopressin, and sodium during endotoxin and endogenous pyrogen induced fever in the goat

Abstract: Responses to intravenous injections of an endotoxin (E. coli-lipopolysaccharide, 1 microgram/kg b.wt.) and endogenous pyrogen were studied in euhydrated and hyperhydrated goats. The biphasic febrile response to the endotoxin was associated with a pronounced increase in the renal excretion of measured prostaglandin (PG) metabolites (11-ketotetranor PGF metabolites). This increase was time-correlated with the elevation of the rectal temperature, and (in hyperhydrated animals) with an inhibition of the water diur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…Bacterial endotoxin increases renal production of prostaglandins, thromboxane, leukotrienes, IL-1 and endothelin [53][54][55]. Endotoxins cause natriuresis, either by direct action [53] or mediated by IL-1 [56].…”
Section: Discussionmentioning
confidence: 98%
“…Bacterial endotoxin increases renal production of prostaglandins, thromboxane, leukotrienes, IL-1 and endothelin [53][54][55]. Endotoxins cause natriuresis, either by direct action [53] or mediated by IL-1 [56].…”
Section: Discussionmentioning
confidence: 98%
“…Beasley et al (1988) reported that IL-1/3 gave rise to natriuresis and diuresis, but not kaliuresis accompanied by increased urinary excretion of PGE2 in conscious rats without a change in renal hemodynamics. Jonasson et al (1984) showed that exogenous and endogenous pyrogens increased urinary excretion of Na and PG metabolites in goats. In these studies, however, the occurrence of increases in urine Na excretion was not in accord with the increased urinary excretion of PGE2 and PG metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…However, the exact mechanisms whereby cytokines increase urinary Na excretion and urine flow remain to be unknown and are still controversial (Gombos et al 1967;Levenson et al 1982; Jonasson et al 1984;Caverzasio et al 1987; Beasley et al 1988;Kohan 1989). Namely, pyrogen and cytokines have been found to stimulate the production of renal prostaglandins (PGs) with resultant increases in renal blood flow and direct inhibition of tubular Na reabsorption, which leads to a natriuresis and diuresis (Jonasson et al 1984; Beasley et al 1988;Kohan 1989). On the other hand, ibuprofen, indomethacin and acetylsalicylic acid, cycloxygenase inhibitors, have been reported to fail to inhibit a cytokine-induced natriuresis (Gombos et al 1967;Caverzasio et al 1987; Beasley et al 1988).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These responses can be related to local inflammatory responses which are induced by mononuclear cell factor (MCF). The elevation of circulating PG's and enhanced renal excretion of PG metabolites, especially during the early phase of fever, might further bear some relationship with altered organ functions during fever, e.g., the sequence of antidiuresis and diuresis observed in goats during endotoxin fever [30] or the dissociation of renal blood flow and local sympathetic activity [41].…”
Section: A Response Components Of the Fever Syndromementioning
confidence: 99%